Critical dimensions in the empirical measurement of common shareholding - Nicoletta Rosati; Pietro Bomprezzi; Maria Martinez Cillero (Research in International Business and Finance, 2024)
The debate on common shareholding and its potential antitrust effects is currently on the agenda of major institutions worldwide. Discussions point to the need for improved empirical quantification of this phenomena. This work presents a flexible, multifaceted statistical framework for a set of new common shareholding indicators, covering both firm and investor perspectives, which can be adopted under different economic models. Many indices currently used in the literature fall within this framework as special cases. Aggregation at market level yields suitable industry-level indicators, providing policymakers with tools to evaluate the extent of common ownership in strategic markets. The indices are tested using firm-level data for European Mobile Network Operators in 2007–2021, showing a sector with concentrated ownership under large corporate groups, but also the presence of institutional investors with extensive ownership across the major firms.
Keywords: C18; D21; D22; G11; G32; L40; 330; Common ownership; Corporate governance; Networks; Mobile network operators; Anti-competitive practices